2017
DOI: 10.1002/14651858.cd011598.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition support in hospitalised adults at nutritional risk

Abstract: There is low-quality evidence for the effects of nutrition support on mortality and serious adverse events. Based on the results of our review, it does not appear to lead to a risk ratio reduction of approximately 10% or more in either all-cause mortality or serious adverse events at short-term and long-term follow-up.There is very low-quality evidence for an increase in weight with nutrition support at the end of treatment in hospitalised adults determined to be at nutritional risk. The effects of nutrition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 538 publications
1
52
0
2
Order By: Relevance
“…Whether acute care clinical dietitians are best placed to resolve the underlying aetiology of malnutrition has been questioned . Malnutrition is a wicked problem .…”
Section: Introductionmentioning
confidence: 99%
“…Whether acute care clinical dietitians are best placed to resolve the underlying aetiology of malnutrition has been questioned . Malnutrition is a wicked problem .…”
Section: Introductionmentioning
confidence: 99%
“…The GRACIA-3 trial is unique in developing this predictive model for several reasons. First of all, it provides the opportunity to compare bare metal stents versus drug eluting stents in a clinical context, ST elevation acute myocardial infarction, where the benefit of new drug eluting stents is still discussed and under comparison [23]. Thus, our predictive model would be specifically useful in this specific scenario.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Another recent Cochrane review investigating medical and surgical inpatients came to similar conclusions, demonstrating a lack of evidence on the effect of nutritional support on outcome. 10 Both reviews also concluded that previous trials were highly heterogeneous in design, target populations and type of interventions, lacked power to demonstrate safety and in aggregate, thus produced inconclusive results. A very recent trial focusing on a specific protein-rich formula reported no difference in the primary combined adverse event outcome, but found lower mortality in patients receiving the nutritional intervention.…”
Section: Current Evidence From Randomized Trialsmentioning
confidence: 99%